An overview of the pharmacological activities of scopoletin against different chronic diseases. (May 2022) - Parama, Dey; Girisa, Sosmitha; Khatoon, Elina; Kumar, Aviral; Alqahtani, Mohammed S.; Abbas, Mohamed; Sethi, Gautam; Kunnumakkara, Ajaikumar B.
Abstract: Chronic diseases are considered a major public health concern worldwide, and most of these diseases like cancer, cardiovascular, metabolic, and neurological disorders occur due to atypical regulation of multiple signaling pathways. It has also been observed that most of the currently approved therapies for these diseases fail to show prolonged efficacy due to their mono-targeted nature and are associated with the development of chemoresistance, thus restricting their utility. The plant-derived compounds, on the other hand, show multi-targeted nature, and thus these phytochemicals have gained wide attention as they offer negligible side effects. The present review aims to recapitulate the potential effects of one such phytochemical, Scopoletin, which was found to have a diverse range of pharmacological activities such as anti-cancer, anti-diabetic, anti-inflammatory, cardioprotective, hepatoprotective, etc. Scopoletin modulated multiple molecular signatures in cancer, including AMPK, EGFR, MAPK/ ERK, NF-κB, PI3K/Akt/ mTOR, and STAT3; regulated the levels of critical markers of metabolic diseases such as ALT, AST, TG, and TC; inflammatory diseases such as ILs and TNFs; neurological diseases such as AChE, etc. thus relieving the symptoms and severity associated with these diseases. Further, this compound has a non-toxic nature and possesses an excellent pharmacokinetic property, which warrants further investigation in clinical settings for developing it as a potential drug. Graphical Abstract: ga1 Highlights: Scopoletin, hydroxycoumarin can exhibit diverse pharmacological actions against various major chronic diseases. Scopoletin can target multiple molecular targets to attenuate disease progression. It is non-toxic in nature and exhibits excellent pharmacokinetic properties.